An innovative scalable climate information service platform for resilient agriculture is now operational in six provinces in the Philippines - Balanza, Jane Girly C. (2023)
The Alliance provided technical backstopping support to the Bicol Region in the Philippines to carry out a users’ need and climate risk assessment in its six provinces to collect essential information such as cropping calendars, historical climate risks, and initial risk responses, to develop climate information service database. This information is available from the Agro-Climatic Advisory Portal – Bicol (ACAP-Bicol), which was initiated and established by the Department of Agriculture –Regional Field Office 5.